2021
DOI: 10.1111/jac.12539
|View full text |Cite
|
Sign up to set email alerts
|

Grain sorghum hybrids under drought stress and full‐irrigation conditions in the Brazilian Semiarid

Abstract: Considered one of the most important cereals in the world, especially in developing countries, grain sorghum [Sorghum bicolor (L.) Moench] is a tropical species belonging to the Poaceae family, widely cultivated for human and animal feed, fodder and biofuel production (Kumar et al., 2011;Souza et al., 2020). It is a C4 metabolism plant, with high photosynthetic efficiency and high tolerance to abiotic stresses, particularly to drought stress (Adams & Erickson, 2017;Schlegel et al., 2018). This crop requires a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…In contrast, plant growth and development, above-ground biomass, and grain production were more affected by early drought stress with a decrease of 62% for stem biomass, 55% for leaf biomass, and 62% for panicle dry weight. Previous studies have also reported a decrement of plant height, above-ground biomass and grain production under early vegetative drought stress conditions [11,30,31]. In this study, the fact that the grain number per panicle was more affected by early vegetative drought compared to late vegetative drought could be explained by the fact that panicle growth starts very early inside the shoot from the growing point differentiation onwards.…”
Section: Drought Stress Effect On Plant Phenology Growth and Developm...supporting
confidence: 52%
“…In contrast, plant growth and development, above-ground biomass, and grain production were more affected by early drought stress with a decrease of 62% for stem biomass, 55% for leaf biomass, and 62% for panicle dry weight. Previous studies have also reported a decrement of plant height, above-ground biomass and grain production under early vegetative drought stress conditions [11,30,31]. In this study, the fact that the grain number per panicle was more affected by early vegetative drought compared to late vegetative drought could be explained by the fact that panicle growth starts very early inside the shoot from the growing point differentiation onwards.…”
Section: Drought Stress Effect On Plant Phenology Growth and Developm...supporting
confidence: 52%
“…The results for DF differ from those obtained by Galicia-Juárez et al (2020), who reported early genotypes with a flowering range of 51 to 71 days, and late genotypes with a range of 72 to 79 days. Early cycle sorghums are tolerant of drought and high temperatures, they can also have higher yields compared to late flowering varieties (Menezes et al, 2021), because early maturing sorghums can evade the stress of a late drought through earlier grain filling, as this becomes a limitation for sorghum production worldwide (Wang et al, 2020). However, late sorghums are characterized by reaching a greater length and diameter of the stem and number of internodes, which are used to produce ethanol because of their high content of juice and sugar (Naoura et al, 2020).…”
Section: Agronomic Parametersmentioning
confidence: 99%
“…This provides the real drought environment; a crop will experience during future production. Menezes et al (2021) evaluated sorghum hybrids in the field under water stress conditions and identified drought-tolerant genotypes with high yield potential.…”
Section: Phenotyping For Drought Tolerance Under Filed Conditionsmentioning
confidence: 99%